Generals against Carbonari: Count Konstantin Benckendorff’s View of 1820 Naples Revolution - O. V. Anisimov (Научный диалог, 2023)
A previously unpublished document from the Russian State Military Historical Archive — a note by Count Konstantin Khristoforovich Benkendorf, brother of Alexander Benkendorf, head of the III department of the Imperial Chancellery, dedicated to the uprising of the Carbonari society in Naples in July 1820 is analyzed in the article. It is shown that the issues raised in it related to the formation of Russia’s position in regard to the constitutional regime in the Kingdom of the Two Sicilies before the congress in Troppau. The author for the first time carried out the contextualization of this document: parallels with other diplomatic reports of this period were revealed; the views of K.H. Benckendorff on the latest Neapolitan history from the end of the 18th century to the constitutional revolution of 1820-1821 were analyzed; his attitude to the Carbonari society and the Neapolitan generals was shown. It is emphasized that his small note was not only descriptive. It is noted that it contained a proposal not to resort to the intervention of the Holy Alliance, but to contribute to the victory in the internal struggle of the generals over the Carbonari. Attention is paid to the peculiarities of archival attribution of the 1950s, when this note was renamed.